over-Storage of Poplar (Populus deltoides) Saplings Affects their Field Performance - Dhiman, R. C.; Gandhi, J. N. (Indian Forester, 2017)
Results of four separate experiments study the effect of duration of storage of poplar (Populus deltoides) saplings (clone Bahar) on their performance are presented. In the first experiment, the saplings were stored under open conditions up to 10 days and subsequently soaked in water for 24 hours before field planting. In the second experiment, saplings were stored under open conditions for seven days and then soaked in fresh water for different durations from 0 hour to 240 hours. In the third experiment, cuttings made from the treated saplings as mentioned in the first experiment, were studied for rooting and shoot growth by placing them in fresh water. The results of the first experiment had non-significant effect on survival, number of sprouts/plant, length of sprout, number of leaves/sprout, length of leaf blade and width of leaf blade in stored saplings up to 3 days after uprooting, whereas, their storage beyond this period significantly reduced survival and also the mean values of other studied parameters. In the second experiment, storage for seven days significantly reduced survival and all other recorded parameters when compared with those freshly uprooted and planted and those stored for 24 hours in fresh water before planting. In the third experiment, observations on rooting of cuttings in fresh water and growth of shoots and other traits were in consonance with the findings of field planted saplings in the first experiment. In the fourth experiment, cuttings made from base to top of the saplings had significant variation in term of cutting thickness, wood thickness, bark thickness, pith width and also in sprouting and growth.